Divestasi PT. Freeport Indonesia - Yoesry, Erni Yoesr (Jurnal Hukum & Pembangunan, 2019)
Indonesia’s natural resources potential especially in mining sector make it becomes hunted by foreign investor, one of them is PT. Freeport Indonesia. Freeport operates in Indonesia under a Contract of Work (KK) which was signed in 1967. In this contract of work, all management and operational matters are handed over to miners. The state has no control over the operation of the company. The State would only receive royalties of the amount that has been determined in contract of work. Mining companies that want to export processed minerals (concentrates) ought to relinquish the status of contract of work into a Special Mining Business License (IUPK), and build a mineral processing and refining facility (concentrate). Article 97 of Law No. 4 of 2009 on mineral and coal mining along with its implementation regulation stipulates about what should be contained in IUPK (Special Mining Business License), one of which is divestment.